The advertisement call of Gastrotheca fissipes Boulenger, 1888 (Anura, Hemiphractidae) with comments on its distribution - de Mira Mendes, Caio Vinicius; Ruas, Danilo Silva; Lourenço-De-Moraes, Ricardo; Rödder, Dennis; Solé, Mirco (Zootaxa, 2012)
Hemiphractidae contains five genera (Frost 2011; Duellman et al. 2011), of which Gastrotheca Fitzinger is the most diverse with 60 species in Central and South America. Eight species of Gastrotheca occur in eastern and southeastern Brazil (Izecksohn et al. 2009; Frost 2011). According to Caramaschi and Rodrigues (2007) a comprehensive analyses of phylogenetic relationships between species of Gastrotheca from the Atlantic Rain Forest of Brazil still remains to be done. Thus, they separated the species of this genus in three phenetic assemblages, of which Gastrotheca fissipes is placed alone in a group. According to Duellman (1984) the distribution of Gastrotheca fissipes ranges from the state of Pernambuco to Espírito Santo. Recently, Izeckson et al. (2009) suggested that the species formerly known as G. fissipes represented two distinct species. They described G. megacephala as a new species occurring from Espírito Santo to southern Bahia and restricted G. fissipes to occur only at the type locality, Igarassú, Pernambuco. In the present study we describe the advertisement call of G. fissipes and compare it with the advertisement call of G. megacephala. Additionally we provide new data on its geographical distribution.